Pelatihan Kepemimpinan dalam Organisasi untuk Memperkuat Kesadaran dan Partisipasi Perempuan Massenrempulu - Jusnawati Jusnawati; Bahrul Amsal; Ashari Ismail (Panrita Inovasi: Jurnal Pengabdian Kepada Masyarakat, 2023)
This service aims to increase the motivation, knowledge and participation of women, especially Massendrempulu students, in leading organizations. This activity was motivated by the lack of motivation, knowledge, and lack of participation by Massendrempulu female students in leading organizations and creating gender-responsive programs. The method used in this activity is to provide strengthening insight in the form of lectures and discussions. The activity participants were cadres of the Massendrempulu Student Association, Ujung Pandang Polytechnic Commissariat. This activity will take place in July 2023 offline in the HPMM dormitory hall. The material presented includes; gender perspective in society, the urgency and strategy of women's leadership, and the role and programs of organizations in addressing gender issues in organizations and society. It is hoped that this activity can increase knowledge and participation in taking responsibility as a leader, as well as produce programs that are gender responsive and empower women. The implications of this service will increase female students' insight and participation in leading organizations and social sensitivity to deal with gender discrimination issues.